Antibiosis effect of wild dry bean accession on the Mexican bean weevil (Coleoptera: Bruchidae) - Cardona, César; Posso G, Carmen Elisa; Kornegay, Julia L.; Valor, José C.; Serrano, Miguel S. (Oxford University Press, 1989)
High levels of antibiosis resistance to the Mexican bean weevil (MBW), Zabrotes subfasciatus (Boheman), and the bean weevil (BW), Acanthoscelides obtectus (Say), in wild dry bean, Phaseolus vulgaris L., accessions were caused primarily by high mortality of late first instars and, to a lesser extent, by high mortality of early second instars, coupled with a significant prolongation of the duration of the first instar. Antibiosis had a significant effect on the fecundity of F, females reared on resistant varieties. Seed integument did not appear to act as a barrier for larvae of the bean weevil. Rearing of both insects on “artificial” seeds further demonstrated that factors responsible for resistance are present in the cotyledons.